Identification and heterologous expression of the actinoallolide biosynthetic gene cluster. (August 2018) - Inahashi, Yuki; Shiraishi, Taro; Také, Akira; Matsumoto, Atsuko; Takahashi, Yōko; Ōmura, Satoshi; Kuzuyama, Tomohisa; Nakashima, Takuji
Abstract Actinoallolides are anti-trypanosomal macrolides isolated from the secondary metabolites of two endophytic actinomycete strains, Actinoallomurus fulvus MK10-036 and K09-0307. A putative actinoallolide biosynthetic gene cluster was predicted from the genome sequence of the strain K09-0307. The gene cluster spans a contiguous 53 kb DNA region that comprises seven genes encoding three PKSs (aalA1, aalA2, andaalA3 ), cytochrome P450 (aalB ), acyl-CoA dehydrogenase (aalC ), crotonyl-CoA reductase (aalD ), and TetR family regulator (aalR ). The entire gene cluster was cloned into a plasmid pYIK1 by assembling DNA fragments, which were obtained from two cosmids containing left and right parts of the gene cluster. Following the introduction of anermE * promoter at 100bp upstream from the start codon ofaalA1, the gene cluster was introduced intoStreptomyces coelicolor M1152. Subsequent LC-MS analysis revealed production of actinoallolide A in the culture broth. Thus, the actinoallolide biosynthetic gene cluster was identified by heterologous expression inStreptomyces .